MEMBANGUN MASYARAKAT MANDIRI MELALUI PEMBANGUNAN DESA BERKELANJUTAN DI DESA BULANGO KECAMATAN BULANGO TIMUR - Titin Dunggio; Lutvia Ladiku; Muhammad Rifki (Journal of Hulonthalo Service Society (JHSS), 2023)
Sustainable village development is a strategy to improve the quality of life of rural communities by optimally utilizing local potential. This journal aims to describe community empowerment efforts in Bulango Village, East Bulango District, Bone Bolango Regency, with a sustainable development approach. This approach does not only focus on physical development, but also the development of mutually supportive social, economic, and environmental capacities. Through the implementation of this program, the community is expected to achieve independence in various aspects of life. These activities include counseling, skills training, and development of environment-based infrastructure that can improve the standard of living and welfare of the community.